Green Tea Mouthwash as an Adjunctive Therapy for Gingivitis Management: A Quasi-Experimental Study - Suci Erawati; Mangatas Halomoan Parluhutan Hutagalung; Angeline Fransisca Panjaitan (Open Access Indonesian Journal of Medical Reviews, 2025)
Gingivitis, a prevalent inflammatory condition affecting the gums, is primarily caused by plaque accumulation. Green tea (Camellia sinensis) has demonstrated anti-inflammatory and anti-bacterial properties, suggesting its potential as an adjunctive therapy for gingivitis management. This study aimed to evaluate the effectiveness of green tea mouthwash in reducing gingival inflammation. This study employed a quasi-experimental design to investigate the effects of green tea mouthwash on gingival inflammation. A total of 30 participants with mild to moderate gingivitis were recruited from the GBI Miracle Service Medan church in Medan, Indonesia. The participants were instructed to rinse their mouths with green tea mouthwash twice daily, after breakfast and before bedtime, for a period of one week. The green tea mouthwash was prepared by steeping one tablespoon of dried green tea leaves in 250 ml of hot water for 5 minutes, and then cooled to room temperature before use. Gingival index (GI) scores were assessed at baseline and after one week of intervention, which involves examining each tooth at four sites (mesial, distal, facial, and lingual) and assigning a score of 0 to 3 based on the severity of inflammation. The study found a significant reduction in gingival inflammation after one week of using green tea mouthwash. The mean GI score decreased from 2.04 ± 0.401 at baseline to 0.91 ± 0.364 after the intervention, indicating a shift from moderate to mild inflammation (p < 0.05). This improvement in gingival health can be attributed to the anti-inflammatory and antibacterial properties of green tea, particularly its catechin content, which has been shown to inhibit the growth of oral bacteria and reduce inflammatory responses. In conclusion, the findings of this study provide further evidence supporting the use of green tea mouthwash as an adjunctive therapy for gingivitis management. Its efficacy in reducing gingival inflammation, coupled with its natural and readily available nature, makes it a promising option for improving oral health.